Hepatic portal venous gas and bacteremia after colonic endoscopic submucosal dissection: A case report. Issue 1 (1st April 2022) - Tomioka, Akira; Narimatsu, Kazuyuki; Chiya, Nanoka; Nishimura, Hiroyuki; Akita, Yoshihiro; Higashiyama, Masaaki; Komoto, Shunsuke; Tomita, Kengo; Hokari, Ryota
Abstract: Hepatic portal venous gas (HPVG) is considered to be a sign of poor prognosis in abdominal diseases and a potentially fatal condition. However, HPVG after colonic endoscopic submucosal dissection (ESD), is an even rarer complication that there is just one report of it at the moment. In this report, we present a case of HPVG and bacteremia that happened a day after colonic ESD in the descending colon. A 79‐year‐old female was referred to perform endoscopic treatment for a 40‐mm elevated tumor in the descending colon and surgery for clinical T1b cancer in the rectosigmoid colon. With a preoperative diagnosis of intramucosal carcinoma in adenoma, we performed ESD using carbon dioxide insufflation. The tumor was resected en bloc without any adverse events including perforation. On the following day, shivering and a fever of 38°C suddenly developed with no abdominal symptoms. Computed tomography revealed the presence of HPVG and gas in the middle colic vein without pneumoperitoneum. The patient was managed conservatively with fasting and intravenous antibiotic treatment. We confirmed the disappearance of the findings with computed tomography on the next day of the first computed tomography and with a colonoscope, we observed the base of ESD ulcer 5 days post‐ESD. HPVG might be treated conservatively, but it might cause more severe conditions such as air embolism, so this rare complication still needs to be thoroughly monitored.